Molecular characterisation of Tyr530Ser and IVS16–1G>T mutations causing severe factor V deficiency - Zheng, Weidong; Liu, Yanhui; Luo, Ying; Chen, Zhihong; Wang, Yan; Zhang, Liyan; Gao, Guoquan; Yao, Zhibin (Thrombosis and Haemostasis, 2010)
Our previous study reported a missense mutation (Tyr530Ser) and a splicing site mutation (IVS16–1G>T) in blood coagulation factor V (FV) gene in a two-year-old Chinese boy. However, the linkage between the mutations and severe FV deficiency and the underlying mechanism has not been elucidated. The present study was designed to investigate the effect of the two mutations and the possible pathogenetic mechanism. FV procoagulant activity showed tremendous decrease in the patient with two mutations. The bioinformatics analyses predicted that IVS16–1G>T mutation may cause the entire exon 17 of FV to be skipped in transcription and thereby result in a deletion mutant. To confirm the predicted results, the fragment of exon 16 to exon 18 containing IVS16–1G>T mutation was obtained by PCR and site-directed mutagenesis. IVS16–1G>T mutant and wild-type constructs were transfected into COS-7 cells. Sequence analysis showed that mutant transcript lacked the entire 180-bp length of exon 17. Moreover, compared to wild-type, the expression of the two mutant proteins was decreased and the procoagulant activity was also reduced when the deletion mutant cDNA and Tyr530Ser site mutant cDNA were transfected into COS-7 cells, respectively. Our results indicate that Tyr530Ser and IVS16–1G>T could be separately responsible for severe FV deficiency, while the phenotype in the proband could be caused by the combination effect of the two defects.
Keywords: Factor V deficiency; splicing mutation; missense mutation; pathogenetic mechanism